STUDI LITERATUR TENTANG KECERDASAN EMOSIONAL REMAJA (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The research was conducted to determine the basic concepts and theories, influencing factors, the impact of positive and negative emotional intelligence, and how to improve adolescent emotional intelligence. The type of research used is literature study. The instrument used in this research is a book, and a combination of national and international journals. The data analysis used is qualitative. The results showed that emotional intelligence is an important ability for individuals to achieve success in learning and in various areas of life that develops throughout life through the learning process. The grand theory for emotional intelligence is Daniel Goleman’s, namely that successful individuals are not only intellectually intelligent but emotional intelligent. The results showed that the factors that affect the emotional intelligence of adolescents in the highest order are family, parents, gender and perrs. Based on the research findings, it is known that there are is a positive impact of emotional intelligence on adolescents, namely good achievement and learning outcomes, while the negative impact is juvenile delinquency. The results of the study show that there are various ways to improve adolescent emotional intelligence, including through counseling and guidance servicesKey Words: Literature study, Emotional Intelligence, adolescents